The Profile of Erythroderma Patients - Shelma Maharani; Trisniartami Setyaningrum (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Erythroderma is a rare, but it is life threatening. By knowing the profile of eritroderma, can expect the management and the cure of the patient more better. Objective: To evaluate the general profile of erythrodermic patients. Methods: This study was conducted retrospectively in erythrodermic patients in Kemuning Ward dr. Soetomo General Hospital Surabaya in 2011- 2014, collecting data from medical records of patients, including the incidence, etiology, clinical features, investigations, treatment, complications, mortality, and return visit. Results: The incidence of erytroderma patient was 83 (5.3%), gender most was men (54.2%) with the highest age range > 60 years (31.3%), the etiology of most was due to drug reactions (39.7%), skin efflorescence highest number was macular erythematous and thin scale, the percentage of each 69 (83.1%) and 65 (78.3%), the majority results of histopathological examination was drug reaction 23 (43.5%) and psoriasis vulgaris 18 (33.9%), patients were receiving oral dexamethasone therapy (80.7%), mostly complications was on the skin (69.9%), mortality rate was 6.1%. Conclusion: The profile of erythroderma patient has already been described, and the management was giving a good outcome with the mortality rate  6,1%.